125 Monocyte subpopulation counts and functional characteristics predict adverse clinical events post ST elevation myocardial infarction. (16th May 2012) - Ghattas, A A; Lip, G Y H; Griffiths, H; Shantsila, E
Abstract : Background: Monocytes are implicated in the initiation of the atherosclerotic plaque through to plaque instability and rupture during presentation with an acute coronary syndrome (ACS). Little is known about the predictive role of monocytes on clinical outcome. We studied the role of the three phenotypically and functionally discrete monocyte subpopulations in predicting major adverse cardiac events (MACE)—defined as recurrent ACS, heart failure and death- following ST elevation myocardial infarction (STEMI). Method: STEMI patients treated with percutaneous revascularisation, were recruited in the first 24 h post-infarction. Peripheral blood monocyte subpopulations were enumerated and characterised using flow cytometry after staining for CD14, CD16 and CCR2. Phenotypically, monocyte subpopulations are defined as: CD14++CD16−CCR2+ (Mon1), CD14++CD16+CCR+ (Mon2) and CD14+CD16++CCR2− (Mon3) cells. Functionally, monocyte subpopulation activation of nuclear factor κ B (NFκB) was analysed. Activation of NFκB was determined by flow cytometry as the mean fluorescent intensity (MFI) of intracellular κ-B kinase β (IKKβ), as a downstream activation product of the NFkB pathway. MACE events were recorded at follow-up. Results: We recruited 96 patients (average age 61.5 years±13.3; 64.6% male). Patients were followed-up for a median of 187 days (112–222 days). MACE events occurred in 14 patients (14.6%). Using logistic regression analysis, increased total monocyte count (p<0.032), Mon2 counts (p<0.047) and Mon3 IKKβ (p<0.013) were significantly predictive of MACE at follow-up (Abstract 125 table 1 ). Mon2 counts were an independent predictor of MACE after adjusting for age and sex. Conclusion: Increased total monocyte and Mon2 counts in the first 24 h post infarction is predictive of MACE in STEMI patients. Mon3, despite an assumed role in reparation and fibroblast deposition, are also predictive of MACE. Monocytes remained functionally active throughout the acute and healing phases, and thus may have prognostic implications.